Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $R$ be a finite ring, and assume $\exists x,y\in R$ such that $ xy=1$. How can I show it implies $yx=1$?

share|improve this question
4  
$ya=yb\Rightarrow y(a-b)=0\Rightarrow xy(a-b)=0\Rightarrow a-b=0\Rightarrow a=b$ –  anon Jul 21 '13 at 10:54

3 Answers 3

up vote 9 down vote accepted

Hint: $xy=1$ implies that left multiplication by $y$ is one-to-one. Can you draw a conclusion whether or not there is a $z$ such that $yz=1$?

If so, you can complete the argument by showing that $z=x$.

share|improve this answer
    
Easy exercise: modify the proof for the case where $R$ is a finite $k$-algebra, where $k$ is field. Hard exercise: find a proof that works for both at once. (Hint: invent $\mathbb{F}_1$.) –  Zhen Lin Apr 29 '12 at 19:37
1  
@Zhen You may find of interest work by Vasconcelos, Armendariz et. al on analogous questions for finitely generated modules. For references see my 2007/12/12 sci.math post –  Bill Dubuque Apr 29 '12 at 20:33

Hint $\ $ As often occurs, this result on numbers is a special case of a result on functions. namely, consider $\rm\:x,y\:$ as left-multiplication maps $\rm\:f(r) = xr,\ g(r) = yr,\:$ then apply the following

Lemma $\rm\ fg = 1\ \Rightarrow\ gf = 1\ $ for maps $\rm\:f,g\:$ on a finite set $\rm\:R.$

$\rm(1)\ \ \ fg = 1\ \Rightarrow\ g\ is\ 1\!-\!1\:$ by $\rm\:f\:$ of $\rm\:g(a) = g(b)\ \Rightarrow\ a = b $

$\rm(2)\ \ \ g\ is\ 1\!-\!1\ \Rightarrow\ g\:$ is onto, since $\rm\:R\:$ is finite

$\rm(3)\ \ \ g\ is\ onto\ \Rightarrow\ gf = 1\:$ by $\rm\ a = g(b) = g(fg(b)) = gf(a)$

Remark $\ $ In fact we may view the ring as the set of such maps (left-regular representation), where the elements of $\rm\:R\:$ are essentially viewed as $1$-dimensional matrices. Then the above is analogous to a well-known result about matrices, e.g. see my post here where I prove $\rm\ AB = I\:\Rightarrow\; BA = 1,\:$ or, equivalently, $\rm\:B\:$ injective $\rm \Rightarrow$ $\rm\: B\:$ surjective, by exploiting the pigeonhole principle. See also other posts in that thread which clarify the fundamental role played by the pigeonhole principle. See also this question on Dedekind-finite rings, i.e. rings where $\rm\:xy = 1\:\Rightarrow\: yx = 1.$

share|improve this answer

Let $f_y\colon:R\rightarrow R,\ z\mapsto yz$ then: $$f_y(z)=f_y(t)\iff yz=yt\Rightarrow x(yz)=x(yt)\Rightarrow (xy)z=(xy)t\Rightarrow z=t$$ hence $f_y$ is one to one. Now since $R$ is finite then the map $f_y$ is bijective hence there's a unique $z\in R$ s.t. $f_y(z)=yz=1$ so $x(yz)=(xy)z=z=x$ and conclude.

share|improve this answer
3  
@YACP If there's a pretty clear comment (and it is) so this forbid me to give an answer ?? –  Sami Ben Romdhane Jul 21 '13 at 11:06
    
Another way to understand this argument is functionally: if left-multiplication by $y$ were non-injective, then post-composing it with left-multiplication by $x$ would necessarily yield a non-injective map, meaning multiplication by $xy$, or $1$, absurd. –  anon Jul 21 '13 at 19:41

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.